Clever Ali - Farmer, Nancy; De Marcken, Gail (New York : Orchard Books, 2006)
When seven-year-old Ali's greedy pet steals cherries from the wicked Sultan for whom his father keeps carrier pigeons, Ali is given three days to find 600 new cherries or his father will be thrown into the deep, dark oubliette. Includes facts about carrier pigeons and the sultan on whom this story is based, as well as an excerpt from "In Praise of Books" by al-Jahiz.
1 12 17 20 23 29 33
Keywords: Homing pigeons -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Sultans -- Juvenile fiction; Egypt -- History -- 640-1250 -- Juvenile fiction; Homing pigeons -- Fiction; Pigeons -- Fiction; Fathers and sons -- Fiction; Kings, queens, rulers, etc. -- Fiction; Egypt -- History -- 640-1250 -- Fiction